CUTANEOUS LESIONS WITH VERY LONG DURATION AS A COMPLICATION OF LEISHMANIZATION - H. Amini (Tehran University of Medical Sciences, 1991)
A list of 28 patients is given in whom the duration of the sore at the site of leishmanization has been 3 to 7 years. The problem of cases of cutaneous leishmanjasis with long duration as a complication of leishmanization is discussed. Although this complication is very rare, i.e. a few hundreds among more than 2 million people inoculated, its effect on the leishmanization program has been Considerable as reflected in reports by dermatologists the situations in which leishmanization is recommended is discussed.